Substance Abuse and Workplace Fraud: Evidence from Physicians - Millar, Melanie; White, Roger M.; Zheng, Xin (Journal of business ethics, 2023)
We examine the relation between worker substance abuse and workplace fraud in a sample of medical doctors. Relative to their peers, we observe that doctors engaging in substance abuse are between 50 and 100 times more likely to commit fraud in a given year. This result is consistent with research suggesting that substance abuse both creates financial pressures and impairs the functioning of cognitive self-regulatory mechanisms. Our results are robust in within-subject tests and between-subject tests, as well as in tests using instrumental variables that exploit exogenous variation in the state-level availability of opioids, a commonly abused substance.